(68)Ga-labelled exendin-3, a new agent for the detection of insulinomas with PET - Brom, Maarten (Springer-Verlag, 2010)
PURPOSE: Insulinomas are neuroendocrine tumours derived from pancreatic β-cells. The glucagon-like peptide 1 receptor (GLP-1R) is expressed with a high incidence (>90%) and high density in insulinomas. Glucagon-like peptide 1 (GLP-1), the natural ligand of GLP-1R, is rapidly degraded in vivo. A more stable agonist of GLP-1R is exendin-3. We investigated imaging of insulinomas with DOTA-conjugated exendin-3 labelled with (68)Ga. METHODS: Targeting of insulinomas with [Lys(40)(DOTA)]exendin-3 labelled with either (111)In or (68)Ga was investigated in vitro using insulinoma tumour cells (INS-1). [Lys(40)((111)In-DTPA)]Exendin-3 was used as a reference in this study. In vivo targeting was investigated in BALB/c nude mice with subcutaneous INS-1 tumours. PET imaging was performed using a preclinical PET/CT scanner. RESULTS: In vitro exendin-3 specifically bound and was internalized by GLP-1R-positive cells. In BALB/c nude mice with subcutaneous INS-1 tumours a high uptake of [Lys(40)((111)In-DTPA)]exendin-3 in the tumour was observed (33.5 ± 11.6%ID/g at 4 h after injection). Uptake was specific, as determined by coinjection of an excess of unlabelled [Lys(40)]exendin-3 (1.8 ± 0.1%ID/g). The pancreas also exhibited high and specific uptake (11.3 ± 1.0%ID/g). High uptake was also found in the kidneys (144 ± 24%ID/g) and this uptake was not receptor-mediated. In this murine tumour model optimal targeting of the GLP-1R expressing tumour was obtained at exendin doses ≤0.1 µg. Remarkably, tumour uptake of (68)Ga-labelled [Lys(40)(DOTA)]exendin-3 was lower (8.9 ± 3.1%ID/g) than tumour uptake of (111)In-labelled [Lys(40)(DTPA)]exendin-3 (25.4 ± 7.2%ID/g). The subcutaneous tumours were clearly visualized by small-animal PET imaging after injection of 3 MBq of [Lys(40)((68)Ga-DOTA)]exendin-3. CONCLUSION: [Lys(40)((68)Ga-DOTA)]Exendin-3 specifically accumulates in insulinomas, although the uptake is lower than that of [Lys(40)((111)In-DTPA)]exendin-3. Therefore, [Lys(40)((68)Ga-DOTA)]exendin-3 is a promising tracer to visualize insulinomas with PET.